HUBUNGAN MINAT BACA CERITA PENDEK DAN KETERAMPILAN MENULIS CERITA PENDEK SISWA KELAS IX SMPN 3 BATUSANGKAR - Lestari, Yulia; Emidar, Emidar; Noveria, Ena (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACT The purpose of this study is as follows. First, describe the interest in reading short story class IX students of SMP N 3 Batusangkar. Second, describe the skills to write a short story class IX students of SMP N 3 Batusangkar. Third, analyze the relationship between interest in reading short stories and short story writing skills class IX students of SMP N 3 Batusangkar. The research data in the form of a score of interest in reading short stories and short story writing skills scores class IX students of SMP N 3 Batusangkar.The results of this study are the following there is a positive and significant relationship between interest in reading short stories and short story writing skills class IX students of SMP N 3 Batusangkar at significant level of 95% and a degree of freedom (df) = n-1 because thitung> ttable ie 6,66> 1 70. Kata kunci: hubungan, minat baca cerita pendek, keterampilan menulis cerita                       pendek